The International Trade in Wastes : a Greenpeace Inventory - International Waste Trade Schemes and Related International Policies - Vallette, Jim; Spalding, Heather (Washington: Greenpeace U.S.A., 1990)
"Compiled by the Greenpeace International Waste Trade Project; Edited by Jim Vallette and Heather Spalding"